Outcome of fractures of dorso lumbar spine treated by short segment posterior stabilization with intermediate pedicle screws - Manikandan, N.; Aloy, Babu (International Journal of Research in Orthopaedics, 2019)
Background: Spine fractures are common in today’s world due to high frequency of motor vehicle accidents and work place injuries. These are major cause of disability in adult population. The mortality rate following spinal injuries is 7%. The aim of the study was to study the functional and radiological outcome of fractures of dorso lumbar spine treated by short segment posterior stabilization with intermediate pedicle screws. Methods: Dorso-lumbar fractures with intact pedicle on the fractured segment, Load sharing classification score of equal or less than 6, Neurologic involvement caused by the fracture, loss of vertebral body height by more than 50% and kyphosis angle more than 20° are included. Patients with multiple level fractures and pathological fractures were excluded from the study. Denis classification and AO classification were used. Load sharing score is used to decision making for intermediate screw fixation. Results: L1 is more frequently fractured followed by D12. Distraction type (AO) and burst (Denis) are most common types. 4 of our patients had complete neurological deficit. 15 had incomplete deficit and 11 patients doesn’t have any neurological involvement. Frankel A grade cases remained in the same grade. Mean Kyphotic correction is 6.7°. Mean AVBCP in the postoperative cases 26. None of the cases developed kyphosis or loss of correction in the follow up. Outcome using Roland Morris disability questionnaire is excellent in 64.3%, good in 21.6% and poor in 14.3% cases. Conclusions: To conclude that short segment posterior stabilisation with intermediate screws provides better biomechanical stability when compared with conventional short segment fixation.